Análise do uso e ocupação do solo e mapeamento de áreas aterradas em Abaetetuba - PA. - SILVA, Thamna Maíra Lourinho (Universidade Federal do Pará, 2019)
On January 4, 2014, in the Municipality of Abaetetuba PA, there was a landfill collapse in the São João Neighborhood, which affected about 67 (sixty-seven) families, so that 13 (thirteen) houses were destroyed and 49 forty-nine) interdicted. According to the Geological Survey of Brazil, the area in which the disaster occurred was gradually landed by irregular residents (with a landfill composed of sand, clay, garbage and açaí stones), and without the proper monitoring of the Public Power. Therefore, the present work has the main objective to perform analysis of land use and occupation - from multitemporal analysis through the algorithm Maximum Likelihood - of the urban area of the municipality, as well as the mapping of land areas along the Preservation Areas Permanent - APP located in the surroundings of the city, based on the delimitations established by the New Forest Code, established by Law Nº. 12.651 of May 25, 2012. It was verified that the urban expansion has intensively pressed this special area and, based on analyzes concerning the use and occupation of the soil, it was verified that in a period of 28 years there was a reduction of 4.01 km2 of vegetation cover and, consequently, the growth of about 4 km2 of deforested areas in favor of urban expansion. When conducting field surveys regarding possible terraced areas around the city, it was concluded that there was grounding in all 14 (fourteen) points visited.